2002
DOI: 10.1074/jbc.m205967200
|View full text |Cite
|
Sign up to set email alerts
|

A Polyamine Analogue Prevents Acute Pancreatitis and Restores Early Liver Regeneration in Transgenic Rats with Activated Polyamine Catabolism

Abstract: We recently generated a transgenic rat model for acute pancreatitis, which was apparently caused by a massive depletion of pancreatic polyamines spermidine and spermine due to inducible activation of their catabolism (Alhonen, L., Parkkinen, J. J., Keinä nen, T., Sinervirta, R., Herzig, K. H., and Jä nne, J. (2000) Proc. Natl. Acad. Sci. U. S. A. 97, 8290 -8295). When subjected to partial hepatectomy, these animals showed striking activation of polyamine catabolism at 24 h postoperatively with a profound decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 22 publications
1
50
0
1
Order By: Relevance
“…In line with the above studies, we found that MeSpd prevents zinc-induced pancreatitis and restores liver regeneration in transgenic rats overexpressing SSAT under the control of the metallothionein promoter (5). Under these conditions where polyamine catabolism was intensely activated, the natural polyamines could not be used as they were rapidly acetylated and degraded with no net tissue accumulation (5).…”
supporting
confidence: 54%
See 4 more Smart Citations
“…In line with the above studies, we found that MeSpd prevents zinc-induced pancreatitis and restores liver regeneration in transgenic rats overexpressing SSAT under the control of the metallothionein promoter (5). Under these conditions where polyamine catabolism was intensely activated, the natural polyamines could not be used as they were rapidly acetylated and degraded with no net tissue accumulation (5).…”
supporting
confidence: 54%
“…Liver regeneration could be fully restored with prior administration of MeSpd (5). Based on these studies and earlier work indicating that partial hepatectomy rapidly elevates the hepatic spermidine, but not spermine, pool, we assigned a critical role to spermidine in liver regeneration (5,18).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations